STYLISTIC FEATURES OF SPORT TERMS - Norqulov Mirali, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This study examines the specialized vocabulary and style of English sports language, drawing on recent linguistic analyses. Sports terminology forms a dynamic, hierarchical system of concepts. Researchers distinguish formal sports terminology (used in rulebooks and coaching) from a broader sports lexicon that includes colloquial expressions and slang. Across journalism, commentary and fan communication, sports language frequently employs vivid rhetorical devices: alliteration, metaphor, epithets, and other figurative figures to heighten excitement. For example, print headlines often use alliteration or hyperbole (“Bulls Battle Back” or “crushing defeat”) to dramatize events. Commentators likewise describe competition in warlike terms (“battle for the top spot”). These devices make sports narratives more engaging and memorable. The specialized lexicon also seeps into everyday English: many idioms (e.g. throw in the towel for “give up”) originate in sports and have broad currency. In sum, sports language blends technical jargon, slang, and creative imagery, with a rich stylistic palette that has attracted increasing attention in discourse studies.